NIlai KONSELING ADAT PADA TRADISI LOMBAN KUPATAN, TAYU, JAWA TENGAH - Nihayah, Ulin (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
ABSTRACT: Indigenous counseling is a form of counseling that promotes cultural and customary identity in community settings, where western counseling has limitations in the context of multiculturalism. This form of indigenization can be seen in the form of traditions that exist in the community, one of which is in the Lomban Kupatan culture, where this tradition involves elements of tradition and ritual as well as social integration of the community. This study uses ethnographic methods where the analysis used uses descriptive analysis, where the researcher wants to interpret behavior patterns, beliefs that exist in this Lomban Kupatan procession in indigenous counseling values, so that information on the implementation of indigenous counseling values in the Lomban Kupatan tradition is obtained. The results of this study provide an overview of the indigenous values that exist in the implementation of Lomban kupatan related to the implementation of individualism values where fishermen believe in marabaya, and Lomban is used as a form of belief in eliminating reinforcements', besides that the second value is the implementation of collectivism where individuals are part of society. do mutual cooperation in the form of cooperation and hospitality in the competition. The indigenous counseling values that are implemented in this Lomban procession, are related to counseling services including: not eliminating trust from the Lomban customary process, the counselor has multicultural knowledge in this case in the Lomban traditional procession and there is acknowledgment of spiritualism in the implementation of Lomban